2009
DOI: 10.1021/jf901559a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Date (Phoenix dactylifera L., Medjool or Hallawi Variety) Consumption by Healthy Subjects on Serum Glucose and Lipid Levels and on Serum Oxidative Status: A Pilot Study

Abstract: The present pilot study analyzed, for the first time, the in vivo effect of Medjool or Hallawi date consumption by healthy subjects on serum glucose, lipids, and oxidative stress. Total phenolics concentration in the Hallawi versus Medjool dates was greater by 20-31%. The major proportion of the soluble phenolics in both date varieties consisted of phenolic acids, mainly ferulic acid and coumaric acid derivatives, and also chlorogenic and caffeic acid derivatives. Unlike the Medjool dates, Hallawi dates contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 33 publications
5
57
2
1
Order By: Relevance
“…The presence of higher phenolic concentration, catechins (antioxidants) as well as the different absorption, metabolism and bioactivity of the various phenolic compounds in Hallavi dates, attributes to the increased antioxidant property, higher FRAP as well as serum high density lipoprotein-associated PON1 activity as compared to the Medjool variety. These results justifies the various in vitro studies; showing that dates in general and the Hallawi variety in particular are beneficial and can be included in our regular diet, without having to worry on its adverse affects (Rock et al, 2009).…”
Section: Clinical Studiessupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of higher phenolic concentration, catechins (antioxidants) as well as the different absorption, metabolism and bioactivity of the various phenolic compounds in Hallavi dates, attributes to the increased antioxidant property, higher FRAP as well as serum high density lipoprotein-associated PON1 activity as compared to the Medjool variety. These results justifies the various in vitro studies; showing that dates in general and the Hallawi variety in particular are beneficial and can be included in our regular diet, without having to worry on its adverse affects (Rock et al, 2009).…”
Section: Clinical Studiessupporting
confidence: 71%
“…Recently, Rock et al (2009) studied the effect of two varieties of dates (Medjool and Hallawi) on serum oxidative status, glucose and lipid levels in healthy human subjects. The volunteers were advised to consume 100 g/day of either variety of dates for a period of 4 weeks, after which they were tested for variations in the mentioned serum parameters.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Other components such as polyphenols, potassium, magnesium, sodium, and vitamins found at low variable concentrations in date may be responsible of the following biological properties. Polyphenols protect against oxidative stress 9 , and possess some anti-high blood pressure effects 10 . The considerable amount of potassium and magnesium has protective role in cardiovascular diseases in general and high blood pressure in particular 11 Ascorbic acid and pyridoxine are able to reduce blood pressure 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The above antioxidant activity is attributed to the wide range of phenolic compounds present in dates, including p-coumaric, ferulic and sinapic acids, as well as flavonoids and procyanidins (30,31) . Aviram et al (32) showed for the first time the in vivo beneficial effect of Medjool or Hallawi date varieties, despite very high content of sugars, consumed by healthy subjects on serum glucose, lipids and oxidative stress. Both date varieties possessed antioxidative properties in vitro, but their antioxidant properties in vivo were unknown.…”
Section: Datesmentioning
confidence: 99%